Rural school and territory: a geography for peace - Vera, Nidia (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2020)
The issues of time and space have been key in the understanding of human life and have a long tradition in the development of human thought; therefore, they have a special role and significance in the development of human culture; this also means that issues related to the spatio-temporal orderings of the various societies become an important part of school work and its educational processes, being Social Sciences the disciplines in charge of these issues. However, the existence of this concern and of this set of disciplines does not translate into the existence of a true and solid training on these issues. In fact, the spatial issue that is evident in the architecture of the institution itself as in the educational proposal, has not generated a formation that leads to a relationship, both conscious about space and its role in personal and social life, as well as about the close relationships that arise between the development model and space and that leads to a more real participation of communities in territorial planning. Therefore, given the circumstances surrounding the Colombian rural world, it would be desirable for the school to review its spatial references and, in view of the post-conflict situation, to participate in the process of re-constituting community-territory links, generating processes of appropriation and consolidation of new spatial arrangements.